Opta Scholar: An Efficient Software for the Bus Routing and Scheduling Problem. Issue 9 (2018) - Oesterle, Jonathan; Chehade, Hicham; Amodeo, Lionel; Yalaoui, Farouk; Prins, Christian
Abstract: While many children walk or cycle to and from school, buses and minibuses are major modes of travel for children. A typical journey of these pupils involves walking to and from the bus stop, waiting at bus stops, and boarding. The school bus routing problem, which consists of a set of students spread in a region who must be brought to and from their schools every school day, is considered in this paper. This paper describes the application of an efficient optimization software, Opta Scholar, to solve the school bus routing and scheduling problem. The application of this software showed major improvements in terms of the number of buses used and travelling costs. Furthermore, the embedded algorithm outperforms existing benchmark results on relaxed forms of the problem.